Romania Judicial Functional Review - World Bank (Washington, DC, 2014)
This review is one of a series of functional reviews commissioned by the Government of Romania (GOR), funded by the European Union, and carried out by the World Bank. It is an element agreed on by the European Union and the Government as part of the post-accession Cooperation and Verification Mechanism (CVM) established to assess further need for reform in the judicial system and to suggest reforms that would ensure Romania's full integration into the European Union system. The objective of the review is to analyze the functioning of institutions of the judicial system in Romania with a view to providing analytical and advisory input to the Romanian authorities as they formulate an action program to improve the performance of the judicial system. The present report covers a large part of Romania's judicial system, a term used here with broad scope. In accord with the terms of reference (appendix one), in addition to the courts, the review covers the Ministry of Justice, focusing on those functions most directly related to the judiciary and to the Public Ministry (PM), the PM itself, and a range of independent legal professionals whose work complements and in some cases replaces that of judges and prosecutors. Within the judiciary, aside from the ordinary courts, the review also addressed the operations of the Superior Council of Magistracy, the Judicial Inspectorate, and the High Court of Cassation and Justice, all of which operate quasi-independently. They have their own budgets and administrative structures, although are still governed by laws on staffing set by Parliament and staffing levels approved by the cabinet. Within the PM, the team also looked at the quasi-independent National Anti-Corruption Directorate.